Individuals with integrity: John Rawls and Buddhism - Phramaha Thainoi Yanamethi (Salangsing); Phra Silasak Sumato (Buntong); Phrakhru Winaithorn Worrachat Thasa (Dhammathas Academic Journal, 2023)
This academic article aims to present the issue of John Rawls and Buddhism in the context of justice. It conducts a study on individuals who embody Rawlsian principles of justice in comparison with Buddhism, analyzing individuals who possess integrity according to Rawls's principles, justice is the righteousness and begins with creating a hypothetical situation. Which it's rational and free individuals jointly choose the principles of justice to be established in society. And then apply them through the social infrastructure by acknowledging that individuals must embody a morality that reflects a commitment to principles of justice affecting others in society, Rawls's principles imply the importance of integrity. As for the principles of morality in Buddhism, they often emphasize the principles of rights and duties. The principle of coexistence in society for individuals developed through the principles of reason, wisdom, and the principles of moral virtue. Which its have an impact on individuals with integrity according to Buddhist principles, encompasses both reasons and emotion concerning the acceptance of rationality. When individuals seek to have integrity or maintain integrity, they must rely on moral consciousness according to the principles of virtue and mindfulness to help stimulate or support the individual's awareness that what they are about to do may be a violation of the rights and freedoms of others, may have consequences of injustice towards society as a whole. Therefore, the rational principles of reasoning by John Rawls align with the principles of Buddhist philosophy, and this alignment is accepted through the rationality of individuals with integrity.